Implementasi Edukasi Apoteker Untuk Meningkatkan Pengetahuan, Kepatuhan Dan Keberhasilan Terapi Pada Pasien Hiperurisemia Di Farmasi Komunitas - Sinaga, Vera Natalia; Wiryanto, Wiryanto; Khairunnisa, Khairunnisa (Journal of Pharmaceutical and Sciences, 2026)
Hyperuricemia is a condition characterized by elevated uric acid levels that may lead to gout arthritis and metabolic complications. Therapeutic success is strongly influenced by patients’ knowledge and adherence, highlighting the important role of pharmacist-led education in community pharmacy settings. This study aimed to evaluate the effect of pharmacist education on improving knowledge, medication adherence, and treatment success among hyperuricemia patients. A quasi-experimental pretest–posttest study with a control group was conducted involving 170 patients (85 intervention and 85 control) recruited through consecutive sampling. The intervention group received structured pharmacist education and counseling, while the control group received usual care. Outcomes were assessed at baseline and after a 14-day follow-up period. Patient knowledge was measured using a validated questionnaire, adherence was assessed using the MARS-5, and treatment success was evaluated through changes in pain intensity (VAS), serum uric acid levels, and treatment satisfaction using the TSQM-9.The Wilcoxon and Mann–Whitney U tests showed significant improvements in the intervention group compared to the control group. The intervention group demonstrated increased knowledge (Δ3.37), improved adherence (Δ3.67), greater reduction in uric acid levels (Δ1.25 mg/dL), more substantial pain reduction—particularly in disruptive pain (37% vs 13%)—and higher treatment satisfaction (95.29% vs 62.35%).In conclusion, a short-term pharmacist-led educational intervention with a 14-day follow-up effectively improves knowledge, adherence, and therapeutic outcomes in hyperuricemia patients in community pharmacies, supporting its feasibility for routine implementation.